การผลิตโปรตีนเซลล์เดี่ยวจากยีสต์ Hansenula polymorpha โดยใช้กลีเซอรอลดิบจากกระบวนการผลิตไบโอดีเซลเป็นแหล่งคาร์บอน - แคทลียา ตาลวงษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
The purpose of this study was to study single cell protein production from crude glycerol by product from biodiesel production plant by Hansenula polymorpha, a yeast capable of utilizing glycerol as a carbon source. Major composition in crude glycerol were determined. It was found that 54.72 % glycerol, 7.05 % oil and 22.16 % moisture (by weight) were present in crude glycerol. Fatty acid profiles in oil present in crude glycerol consisted of 41.88 % palmitic acid (C16:0), 40.84 % stearic acid (C18:0) and 4.82 % oleic acid (C18:1). From elemental analyses, crude glycerol also contained 44.13 % C, 9.03 % H, 1.34 % N, 1.60 % Na, 39 ppm Cl, 37 ppm K, 15 ppm Ca, 12 ppm Fe, 8 ppm Cu and 4 ppm Zn. Less than 30 ppb β-carotene was detected in crude glycerol. Effects of crude glycerol concentration, nitrogen source, temperature, pH and rotational speed on fermentation of H. polymorpha were investigated. It was found that the maximum cell concentration was obtained from fermentation using 7.5 % crude glycerol and 2 % yeast extract at 30 0C, pH 6.0 and 250 rpm. At this condition, the maximum cell concentration of 32 g/L, the biomass yield of 0.7132 and the productivity of 0.5026 g/L.h were obtained. Wet cell biomass contained 72.34 % moisture. The protein, lipid and carbohydrate contents in dry cell biomass were determined. It was found that the obtained cell contained 41.67 % protein, 16.49 % lipid, 3.08 % ash and 38.76 % carbohydrate. Besides, 0.9 ppm vitamin B2 , 2.0 ppm vitamin B5, 32.5 ppm Vitamin B8, 84.9 ppm vitamin B9 were found in cell sample, where only less than 0.1 ppm vitamins B1, B3 B6, and B12 were found. In addition, 9 of 18 essential amino acids were found in cell biomass including Histidine, Isoleucine, Leucine, Lysine, Methionine, Phenylalanine, Threonine, Tryptophan and Valine. Among the amino acids present in the biomass, up to 72 % of essential amino acids were present (2760.81 mg/100 g dry cell mass)